DINAMIKA PERNIKAHAN TANPA ANAK (CHILDFREE) DALAM TINJAUAN MAQASID SYARIAH: ANTARA HAK PERSONAL DAN KEBERLANJUTAN PERADABAN - Muhammad Ahmad Fulka Sa'dibih (LPPM Universitas Uluwiyah Mojokerto, 2025)
The childfree phenomenon triggers tension between individual autonomy and the procreative objectives of marriage in Islam. This study analyzes the phenomenon through the lens of Maqāṣid al-Sharī’ah, specifically focusing on the protection of offspring (ḥifẓ al-nasl). The results indicate that the choice to permanently abstain from having children without a pressing reason (ḍarūrah) undermines the horizontal essence of marriage, which is to preserve the human race and build civilization. Although Islamic law is flexible, the collective interest (maṣlaḥah) for the sustainability of the Ummah must be prioritized over personal preferences in the absence of valid medical or psychological justifications. Education on the philosophy of the family is crucial for strengthening social structures and national resilience.